Study on Temperature Characteristics of Hydrate Slurry during Cyclopentane-Methane Hydrate Formation - Cai, Jing; Hu, Ya-Fei; Zhang, Yu; Xu, Chun-Gang; Chen, Zhao-Yang; Lv, Qiu-Nan; Li, Xiao-Sen (Energy & Fuels, 2018)
In this work, the temperature characteristics of hydrate slurry related to transition heat in the cyclopentane (CP)/methane (CH4) hydrate formation process were systematically investigated. A crystallizer with a special heat-insulating layer of aerogel was designed to hold the transition heat, and the hydrate slurry could be heated in the crystallizer. Temperatures were measured in the process of the hydrate formation under the conditions of different operating pressures, volumes of solution, methods of gas injection, and volume ratios of CP to water. The highest temperature of hydrate slurry (T-h) and the maximum temperature difference (Delta T-max) relative to the initial temperature were adopted to evaluate the influence of different conditions. The experimental results indicated that the hydrate formation interface and thermal interface obviously move from the initial gas/CP interface and CP/water interface toward the bulk solution. Both the increase of operating pressure and the decrease of solution volume have positive effect on enhancing the hydrate slurry temperature. In addition, the volume ratio of CP to water also significantly affects the fluctuation of the hydrate slurry temperature. The hydrate slurry could be heated up to 294.45 K and the Delta T-max of 16.30 K could be obtained, and such high heat could be effectively collected and used elsewhere.